Study on vinyl crosslinking and related properties of silicon-containing arylacetylene resin synthesised by zinc powder catalysis. (June 2022) - Dong, Sensen; Chen, Fan; Wang, Guihui; Hu, Wei; Zhao, Chuanqing; Hu, Yanhong; Deng, Shifeng
A matrix resin poly(silicon-containing arylacetylene vinyl)s (PSAV) containing vinyl at both branch and terminal chains underwent synthesis via the zinc powder catalytic method using m-diacetylene benzene and dichloromethylvinylsilane as raw materials. Vinyl in the PSAV resin was crosslinked by the free radical initiator dibenzoyl peroxide to obtain a crosslinked network structure resin (PSAV-L). This approach sought to improve the thermal properties and other related properties of the matrix resin. A series of tests, such as rotated rheometer, FTIR, DSC, TGA, Py-GC-MS and universal testing machine, characterised processing property, curing behaviour, thermal properties and mechanical properties. The rheological curve shows that PSAV-L resin has a wide processing window (40–134.5°C), endowing the resin with excellent processing performance. Thermal curing behaviour indicates that PSAV-L resin can start curing at a lower temperature, namely, 32°C earlier than PSAV resin. TGA analysis shows that the degradation temperature at 5% weight loss (Td5 ) of PSAV-L resin stands at 579.4°C, 45.4°C higher than that of PSAV resin due to the fact that the crosslinking of vinyl gives PSAV-L resin a network structure. The flexural strength, flexural modulus and ILSS of the quartz fibre cloth reinforced PSAV-L resin composite (QF/PSAV-L) are 184.68 MPa, 15.50 GPa and 12.40 MPa. The PSAV-L resin exhibits the comprehensive properties of good processing performance, low curing temperature, excellent thermal performance and high mechanical properties.